Tubulointerstitial Nephritis and Uveitis Syndrome in a Twelve-Year-Old Girl. (18th April 2013) - Paladini, Alessia; Venturoli, Vittorio; Mosconi, Giovanni; Zambianchi, Loretta; Serra, Luigi; Valletta, Enrico
Abstract : Tubulointerstitial nephritis and uveitis (TINU) syndrome is a rare disorder defined by the combination of biochemical abnormalities, tubulointerstitial nephritis, and uveitis. We describe a 12-year-old female, presented with a ten-day history of fever, characterized by sudden onset and rapid spontaneous resolution in few hours, accompanied by shivering, extreme fatigue, and loss of appetite. Laboratory values were consistent with renal failure of tubular origin. Renal biopsy confirmed a tubulointerstitial nephritis, with acute tubulitis, polymorphonuclear infiltration, and microabscesses. The renal interstitium was occupied by a dense inflammatory infiltrate, consisting of lymphocytes, plasma cells, and neutrophils. Glomerular structures were preserved. Ophthalmological examination that suggested a previous asymptomatic bilateral uveitis and HLA typing (HLA-DQA1*0101/0201 and HLA-DQB1*0303/0503) further supported the suspect of TINU syndrome. TINU syndrome is probably an underdiagnosed disorder, responsible for many cases of idiopathic anterior uveitis in young patients, especially in those who have asymptomatic renal disease and when proper diagnostic tests are not performed at the time of presentation.